Correlation between dietary score and depression in cancer patients: Data from the 2005–2018 National Health and Nutrition Examination Surveys - Xu, Nan; An, Qing (Frontiers in Psychology, 2022)
Aim: To investigate the correlation between dietary score and depression in cancer patients. Methods: In this cross-sectional study, data came from the National Health and Nutrition Examination Survey (NHANES) 2005-2018, a cross-sectional and nationally representative database, to compare 322 patients with depression to 2,868 with no depression. Mediterranean (MEDS) diet, Dietary Approaches to Stop Hypertension (DASH) diet, and the Healthy Eating Index 2015 (HEI-2015) score were calculated. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9). Weighted logistic regression models were used to explore the relationship between dietary scores and depression in cancer patients. Subgroup analysis was performed by sleep disorders, sex, cancer type, number of tumours, and pain relief prescription treatment. Results: The final study sample included 3,190 adults, with 56.94% of them being women, representing 2,177 (86.51%) non-Hispanic white adults. After multivariable adjustment, MEDS score was correlated with a reduced risk of depression in cancer patients [odds ratio (OR): 0.90, 95% confidence interval (CI): 0.82-0.97, P=0.010]. Moreover, MEDS score correlated with depression in cancer patients with sleep disorders (OR: 0.84, 95%CI: 0.76-0.93, P=0.001), in female patients with cancer (OR: 0.83, 95%CI: 0.74-0.92, P<0.001), particularly in female cancer reproductive system patients (OR: 0.69, 95%CI: 0.57-0.82, P<0.001). MEDS score also showed a decreased risk of depression in patients with 1 cancer (OR: 0.90, 95%CI: 0.82-0.98, P=0.019). MEDS score (OR: 0.86, 95%CI: 0.86-0.98, P=0.024) and DASH (OR: 0.91, 95%CI: 0.84-0.98, P=0.015) score was related to a decreased risk of depression in cancer patients using pain relief prescription. Conclusion: Good diet quality is significantly correlated with decreased risk of depression in cancer patients. Aligning with the Dietary Guidelines, like MEDS diet may be beneficial to the reduced risk of depression in cancer patients.